2021
DOI: 10.1002/uog.23130
|View full text |Cite
|
Sign up to set email alerts
|

Association between 3D endovaginal and 2D perineal pelvic floor ultrasound findings and symptoms in women presenting with mid‐urethral sling complications

Abstract: This is a prospective cross-sectional description of pelvic floor ultrasound (US) findings in 311 women with complications after mid-urethral synthetic slings (MUS). The association between perineal and endovaginal ultrasound scan findings and patient symptoms in a cohort of women with complications after MUS has not been shown before. What are the clinical implications of this work? This study adds to the limited body of evidence for best practice in the assessment of complications after MUS. As recurrent uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was found that the likelihood of experiencing voiding dysfunction was significantly higher in women categorized as having a Group III MUS shape (C-shaped both at rest and during Valsalva), with 64% of these patients affected. Conversely, voiding dysfunction was observed in only 36% of the patients who were part of Group I, where the MUS remained flat during both rest and Valsalva maneuver [71].…”
Section: Urinary Retention and Obstructive Voidingmentioning
confidence: 85%
See 1 more Smart Citation
“…It was found that the likelihood of experiencing voiding dysfunction was significantly higher in women categorized as having a Group III MUS shape (C-shaped both at rest and during Valsalva), with 64% of these patients affected. Conversely, voiding dysfunction was observed in only 36% of the patients who were part of Group I, where the MUS remained flat during both rest and Valsalva maneuver [71].…”
Section: Urinary Retention and Obstructive Voidingmentioning
confidence: 85%
“…The analyses included the sling's distance from the urethral lumen, its position along the urethra, and its shape. No specific US characteristics or measurements correlated with the presence of pain, including dyspareunia [71]. Recently, another group yielded comparable results.…”
Section: Painmentioning
confidence: 98%
“…It is hypothesized that if the sling is overly tense, this might lead to its forward movement toward the region of fixation, such as the obturator foramen in mini-slings. A recent review of ultrasonographic findings of MUS after placement indicated that different sling tension and positioning related to the urethra may result in different surgical outcomes [28].…”
Section: Discussionmentioning
confidence: 99%